Gondolatok az agrárgazdaság regionális fejlesztési koncepciójához - Dorgai, László (Tér és Társadalom, 1996)
The Parliament passed the Act on Regional Development and Physical Planning in the spring of 1996, with the purpose to support a regional development more proportionate than the previous ones in Hungary. A regional development concept for Hungary is prepared based on the Act, containing the concepts of the specific branches of the economy. This short essay gives some thoughts for the creation of the concept of the agriculture. It takes the factors and conditions to be evaluated during the creation of the concept into consideration: large agricultural areas, favourable endowments for produc- tion, state of the natural environment, the role of agriculture in the economic life of Hungary, the geographical location of Hungary, the situation of employment, unemployment, the state of the agricultural machinery, the connection of production and the settlements, and the present spatial structure of agriculture. It outlines the changes necessary in the land use, coming from the different endowments and conditions: profit-oriented agriculture in areas with favourable endowments, in areas with special endowments production of specific products, extensive agriculture for the utilisation of marginal areas, a social type agriculture in micro regions struck by unemployment, agriculture producing for family needs in areas badly provided with retail shops, withdrawing agriculture in lands with the worst quality. It shows regional sectoral objectives of the agriculture, forestry and food processing industry. As agriculture has a strong and organic connection with rural areas, the essay examines the development of the agriculture as part of the logical system of rural development.